2018
DOI: 10.1101/502807
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide Association Study of Multisite Chronic Pain in UK Biobank

Abstract: Chronic pain is highly prevalent worldwide, contributing a significant socioeconomic and public health burden. Several aspects of chronic pain, for example back pain and a severity-related phenotype, chronic pain grade, have been shown to be complex, heritable traits with a polygenic component. Additional pain-related phenotypes capturing aspects of an individual's overall sensitivity to experiencing and reporting chronic pain have also been suggested. We have here made use of a measure of the number of sites … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(78 citation statements)
references
References 134 publications
6
66
3
Order By: Relevance
“…Another approach recently applied in GWAS of chronic pain is based on obtaining a phenotype of multisite chronic pain (MCP) as a sum of the number of anatomical sites affected by pain (a study by Johnston et al 66 ). Johnston et al carried out a large-scale GWAS of MCP in~380,000 UK Biobank participants.…”
Section: Discussionmentioning
confidence: 99%
“…Another approach recently applied in GWAS of chronic pain is based on obtaining a phenotype of multisite chronic pain (MCP) as a sum of the number of anatomical sites affected by pain (a study by Johnston et al 66 ). Johnston et al carried out a large-scale GWAS of MCP in~380,000 UK Biobank participants.…”
Section: Discussionmentioning
confidence: 99%
“…All of these regions have been previously implicated in the modulation of pain (4346), and also concur with the tissue expression analysis (Figure 2, Figure 3) which suggests that the central nervous system modulates neck or shoulder pain. A recent GWAS study suggested that FOXP2 is a candidate gene for multisite chronic pain (47). Further studies into the location and function of the transcription targets of FOXP2 would also provide valuable insight.…”
Section: Discussionmentioning
confidence: 99%
“…Large sample size GWAS summary data on chronic pain and sleep disturbance were used to explore their genetic correlations. The GWAS summary data of chronic pain was from a multisite GWAS of chronic pain in the UK Biobank, which included~380,000 participants 11 . The PSQI is a widely used measure of sleep quality with high sensitivity (98.7%) and specificity (84.4%) 40 for identifying primary insomnia 33,41,42 .…”
Section: Gwas Summary Statistics Data Of Chronic Pain and Sleep Distumentioning
confidence: 99%